One Belt One Road : China's Marshall Plan - Robinson-Parent, Jacob; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This research is aimed at analyzing how China’s One Belt One Road (OBOR) initiative is not so difference from the United States Marshall Plan which aimed to gain influence over European nations. The Marshall Plan of the late 1940’s used monetary stimulus and economic influence to sway some of the war stricken European nations away from the adoption of communism and towards the formation of democratic governments and allies. The OBOR appears to have even less political ambitions but a change in the geopolitical influence seems likely in Central Asia. Part of Central Asia is historically the Soviet Union’s backyard and India’s presence is also noticeable as the other major player of the region. The remainder of the region is mainly unstable and conflict driven. But with economic stimulus and easier access to the European and Chinese market, it seems likely that a lot of change will come to central Asia in the coming decade. The main aim will be to find out how similar these two initiatives are and look at what OBOR will do to Central Asia's economies and political relationship with China.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses